PEMBENTUKAN NILAI-NILAI INTEGRITAS DAN PROFESIONAL MELALUI BIMBINGAN TEKNIS OLEH KPU KOTA PADANG - Zamzami Zamzami; Nursyirwan Efendi; Jendrius Jendrius (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
This research analyzes the value of integrity and professionalism for the election organizers by Padang City KPU through Technical Guidance as an HR development program for election organizers in the Election of West Sumatra 2015 Election. Researchers assume, if the Election organizer Technical Guidance is not managed well, it will have an impact on the weak understanding of the election organizers on the procedural procedures for electoral work and the election organizer's rules. This study uses a qualitative approach, data collection using in-depth interview techniques for 22 informants and supported by documentation studies. The research data was processed and analyzed descriptively, using Mozafard and Scedler's theory of Electoral Governance. The results showed that the Governance of Technical Guidance by the KPU of Padang City had not run as expected, both at the rule making level and the application rule level. But at the level of Adjudication KPU Padang City has done several steps to settle. The effectiveness of Technical Guidance is considered low because there are several weaknesses found: 1.) Achievement targets and material content have not been balanced between procedural work and the formation of the election organizers' attitudes; 2.) There has been no effort to increase the capacity of competent resource persons; 3.) Learning methods, duration of time, training places and other supporting facilities have also not received special attention by the KPU of Padang City. For better management of Technical Guidance, KPU is advised to have a comprehensive curriculum and technical guidelines.